ExCEL in Social Work: Excellence in Cancer Education & Leadership An Oncology Social Work Response to the 2008 Institute of Medicine Report: Cancer Care for the Whole Patient: Meeting Psychosocial Health Needs - Otis-Green, Shirley (J Cancer Educ, 2015)
ExCEL in Social Work : Excellence in Cancer Education & Leadership was a multi-year National Cancer Institute (NCI)-funded grant for the development and implementation of an innovative educational program for oncology social workers. The program’s curriculum focused upon six core competencies of psychosocial-spiritual support necessary to meet the standard of care recommended by the 2008 Institute of Medicine (IOM) Report: Cancer Care for the Whole Patient: Meeting Psychosocial Health Needs. The curriculum was delivered through a collaborative partnership between the City of Hope National Medical Center and the two leading professional organizations devoted exclusively to representing oncology social workers - the Association of Oncology Social Work and the Association of Pediatric Oncology Social Workers. Initial findings support the feasibility and acceptability of this tailored leadership skills-building program for participating oncology social workers.